Health and wellbeing of Māori secondary school students in New Zealand: Trends between 2001, 2007 and 2012. (29th October 2018) - Clark, Terryann C.; Le Grice, Jade; Moselen, Emma; Fleming, Theresa; Crengle, Sue; Tiatia‐Seath, Jemaima; Lewycka, Sonia
Abstract: Objective: To describe the health status over time of Māori secondary school students in New Zealand compared to European students. Methods: Anonymous representative health surveys of New Zealand secondary school students were conducted in 2001, 2007 and 2012 (total n=27, 306 including 5, 747 Māori). Results: Compared to 2001, Māori students in 2012 experienced improved health, family and school connections. However, considerable inequity persists with Māori students reporting poorer health, greater exposure to violence and socioeconomic adversity compared to European students. When controlling for socioeconomic deprivation, inequity was substantially reduced, although worse Māori health outcomes remained for general health, mental health, contraceptive use, healthy weight, substance use, access to healthcare and exposure to violence. There was some evidence of convergence between Māori and European students on some indicators. Conclusions: There have been significant improvements for Māori youth in areas of health where there has been investment. Priority areas identified require adequate resourcing alongside addressing systematic discrimination and poverty. Implications for public health: Socioeconomic contexts, discrimination, healthcare access and identified priority health areas must be addressed to improve equity for Māori youth. Building on these gains and hastening action on indicators that have not improved, or have worsened, is required.